Evaluasi Kecernaan In Vitro Bahan Kering, Bahan Organik dan Protein Kasar Penggunaan Kulit Buah Jagung Amoniasi dalam Ransum Ternak Sapi - Jul Andayani (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2010)
An experiment was conducted to evaluate ammoniated corn husk  in vitro digestibility in  cattle  ration.   Measured  parameters  in  the  current  experiment were    in vitro  digestibility  of     dry matter, organic matter,  crude  protein.  This  study was  assigned  into  completely  randomized  design  (CRD) with  5  treatments  and  4  replications. The  treatments were  ; T0 =  70% Forage  (100%  grass +  0% ammoniation of  Corn husk) + 30 % Concentrate,  T1 = 70% Forage (75 % grass + 25% ammoniation of Corn husk) + 30 % Concentrate, T2 = 70% Forage (50% grass + 50% ammoniation of Corn husk) +  30 %  Concentrate,  T3  =  70%  Forage  (25%  grass  +  75%  ammoniation  of  Corn  husk)  +  30 % Concentrate, T4 = 70% Forage (0% grass + 100% ammoniation of Corn husk) + 30 % Concentrate.  Result of this study showed  that the treatments were  significantly (P<0,05) influence digestibility of dry matter, organic matter and crude protein. Increased level of   ammoniated corned corn husk made higher  in  vitro  digestibility  of  ration.    It  concluded  that  ammoniation  of    corn  husk  could    increase digestibility and th eammoniated  corn husk  may substitute forage in cattle ration.